2017
DOI: 10.2106/jbjs.16.00733
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Surgical-Site, Multimodal Drug Injection Following Operative Management of Femoral Fractures

Abstract: Therapeutic Level I. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Regarding the results from this study and the previous studies on PMDI in hip fracture. Our findings on the additional benefits of PMDI are comparable to the results of previous studies by Kang et al [23] and Koehler et al [24]. In 2013, Kang et al presented a singleblinded randomized controlled trial (RCT) that studied the effect of multimodal pain management in 82 elderly hip fracture patients undergoing bipolar hemiarthroplasty by comparing between those who received combined preemptive medication (10 mg oxycodone SR and 200-mg celecoxib) with intraoperative periarticular injection (100 mL cocktail solution of 300 mg ropivacaine, 10 mg morphine sulfate, 30 mg ketorolac, 300 -mcg epinephrine, 1000 mg cefmetazole, and physiologic saline) (n = 43) and those who did not receive (n = 39).…”
Section: Cas Pmdi Group (N = 12)supporting
confidence: 92%
“…Regarding the results from this study and the previous studies on PMDI in hip fracture. Our findings on the additional benefits of PMDI are comparable to the results of previous studies by Kang et al [23] and Koehler et al [24]. In 2013, Kang et al presented a singleblinded randomized controlled trial (RCT) that studied the effect of multimodal pain management in 82 elderly hip fracture patients undergoing bipolar hemiarthroplasty by comparing between those who received combined preemptive medication (10 mg oxycodone SR and 200-mg celecoxib) with intraoperative periarticular injection (100 mL cocktail solution of 300 mg ropivacaine, 10 mg morphine sulfate, 30 mg ketorolac, 300 -mcg epinephrine, 1000 mg cefmetazole, and physiologic saline) (n = 43) and those who did not receive (n = 39).…”
Section: Cas Pmdi Group (N = 12)supporting
confidence: 92%
“…O'Neill 15 reported that continuous ropivacaine infiltration in the first 48 hours achieved better analgesia, with fewer side effects and a shorter hospitalization duration after cesarean delivery. Koehler 16 conducted a randomized controlled trial and concluded that surgical-site injection alleviated postoperative pain and reduced opioid utilization on the first day postoperatively without major adverse events in femoral fracture patients undergoing surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 23 24) Although various pain control protocols have evolved over recent years for patients with musculoskeletal trauma, surgical-site, multimodal drug injection has been reported to be progressing recently as a new analgesic method after the surgical treatment for musculoskeletal trauma. 22 25 26 27) To the best of our knowledge, this investigation is the first study to assess the effect and safety of the surgical-site multimodal drug injection on the mid-shaft clavicular fractures, along with the evaluation of stress biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“… 22) The SI can preserve motor functions, which may enable early mobilization and limit the side effects associated with systemic narcotics. 27) The preservation of the motor functions with the SI technique may lead to a decreased prevalence of in-hospital falls as compared to that occurring from peripheral nerve blocks. 27) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation